The Portrait of Yossi's Struggle to Survive in The Film Jungle Directed by Greg Mclean - Mutiara Wardah Layalina (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This research describes the form of the main character's struggle to survive in the forest in the film Jungle directed by Greg Mclean which was released in 2017. This film shows the struggle and hard work of Yossi's character to live and get out of the Amazon wilderness where he got lost. In analyzing this study, researchers used descriptive qualitative research methods by making thorough observations and identifying dialogue and visual images in the Jungle film. The approach used is a literary psychology approach by applying the theory of Individual Psychology from Alfred Adler. The purpose of this study is to identify and classify the forms of struggle and the ways in which Yossi figures keep them alive. The results obtained in this study are the forms of struggle for survival of the character Yossi in the film Jungle. Keywords: Struggle, Individual Psychology, Alfred Adler, Main Character, Film